Structural health monitoring 2015 : system reliability for verification and implementation - Chang, Fu-Kuo; Kopsaftopoulos, Fotis (Destech Publications, 2015)
Annotation *Selected research on the entire spectrum of structural health techniques and areas of application*Available in print, complete online text download or individual articles. Series book comprising two volumes provides selected international research on the entire spectrum of structural health monitoring techniques used to diagnose and safeguard aircraft, vehicles, buildings, civil infrastructure, ships and railroads, as well as their components such as joints, bondlines, coatings and more. Includes special sections on system design, signal processing, multifunctional materials, sensor distribution, embedded sensors for monitoring composites, reliability and applicability in extreme environments. The extensive contents can be viewed below. Research in these volumes was initially presented in September 2015 at the 10th International Workshop on Structural Health Monitoring (IWSHM), held at Stanford University and sponsored by the Air Force Office of Scientific Research and the National Science Foundation.
"Proceedings of the 10th International Workshop on Structural Health Monitoring, Stanford University, Stanford, CA, September 1-3, 2015."
Keywords: Structural health monitoring -- Congresses.; Structural analysis (Engineering) -- Congresses.; Reliability (Engineering) -- Congresses.; Detectors -- Congresses.; Automatic data collection systems -- Congresses.; elektronické knihy; electronic books